Multimode quasi-phase-matching of high-order harmonic generation in gas-filled photonic crystal fibers - Anderson, P; Wiegandt, F; Yu, F; Treacher, D; Lloyd, D; Mosley, P; Hooker, S; Walmsley, I (Institute of Electrical and Electronics Engineers, 2017)
Driving bright high-order harmonic generation (HHG) with few-μJ pulses is a crucial step towards compact, high average power sources of coherent extreme ultraviolet (XUV) radiation for time-integrated applications including imaging. Unfortunately, reaching a sufficiently strong E-field to perform HHG with these pulses requires tight focusing, greatly reducing the interaction volume. An elegant solution to this problem is to restrict HHG to a hollow waveguide [1] and in particular a photonic crystal fiber [2]. Strong reabsorption in the XUV prohibits the use of multi-atmosphere pressures to achieve phase-matching [3], and instead quasi-phase-matching (QPM) is preferred. Here we demonstrate QPM of HHG for the first time within a gas-filled PCF.